2004
DOI: 10.1007/s11661-004-0235-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the peritectic reaction in medium-alloy steel through microsegregation and heat-of-transformation studies

Abstract: In the present work, the phenomenon of the peritectic reaction was characterized in a medium-alloy steel. Several directional solidification and thermal-analysis experiments were done to investigate the reaction process. Directional solidification experiments carried out did not tend to show any direct evidence of a peritectic reaction. Microsegregation studies on the directionally solidified samples and those solidified under isothermal conditions bring out some interesting features. It has been documented th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…It can be seen that the growth rate is very high at the start of the peritectic transformation due to the small initial thickness of the layer, d c , which dominates Eqs. [4] and [5]; as the layer gains thickness, the growth rate rapidly drops. It can also be seen that the layer grows into the melt at a considerably higher rate than it does toward d. Figure 11 shows a comparison between the calculated migration distances of the c layer toward d and toward the melt and the migration distances previously observed by Shibata et al [5] The calculated distances show good agreement with the observed ones, indicating the validity of the preceding C-diffusion models in predicting c growth during peritectic transformations in Fe-C systems.…”
Section: Rate Of the Peritectic Transformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen that the growth rate is very high at the start of the peritectic transformation due to the small initial thickness of the layer, d c , which dominates Eqs. [4] and [5]; as the layer gains thickness, the growth rate rapidly drops. It can also be seen that the layer grows into the melt at a considerably higher rate than it does toward d. Figure 11 shows a comparison between the calculated migration distances of the c layer toward d and toward the melt and the migration distances previously observed by Shibata et al [5] The calculated distances show good agreement with the observed ones, indicating the validity of the preceding C-diffusion models in predicting c growth during peritectic transformations in Fe-C systems.…”
Section: Rate Of the Peritectic Transformationsmentioning
confidence: 99%
“…Dhindaw et al [4] conducted differential thermal analysis (DTA) experiments on medium-alloy steels and observed that the heat released during peritectic reactions was considerably lower than that calculated kinetically. They proposed that the difference in energies was due to creep yielding and vacancy formation at the d/c interface, which accommodated for the difference in molar volume between the two phases.…”
Section: Introductionmentioning
confidence: 99%
“…The details of the DTA have been described elsewhere [7]. In brief, the DTA equipment consists of a resistance furnace that heats and cools the sample at a controlled rate.…”
Section: Experimental Workmentioning
confidence: 99%
“…This suggests that the peritectic reaction is not controlled by carbon diffusivity in the liquid, but perhaps by either massive transformation of d into g, or direct solidification of g from the liquid. Support of theses hypotheses was brought recently by the experimental work of Dhindaw et al 16) who studied the peritectic reaction in medium-alloy steel (0.22 mass% C, 1.3 mass% Cr, 2.6 mass% Ni). Microsegregation measurements on directionally and isothermally solidified samples showed that when the segregation ratio for Ni was higher than that fro Cr a peritectic reaction has occurred.…”
Section: The Rate Of the Peritectic Reactionmentioning
confidence: 92%